Significance of muscularis mucosae in metastasis involvement of urinary bladder transitional cell carcinoma - Suchart Chaimuangraj (2018)
Objective: To assess the significance of muscularis mucosae involvement in metastasis of urinary bladder transitional cell carcinoma. Material and Method: This was a retrospective cohort study of superficial urothelial carcinoma (transitional cell carcinoma). Histopathology and patient records of 192 patients were collected from 1990 to 2004. There were 115 males and 77 females, their age ranged from 43 to 83 years old with an average of 60 ± 5 years. One hundred cases did not invade muscularis mucosae layer (group A) and 92 cases invaded the muscularis mucosae layer (group B). The histopathology of biopsy or cystectomy specimens for recurrence, progression of the disease and the number of vessels above and below the muscularis mucosae layer of bladder cancer specimens were compared by light microscopic examination with Hematoxylin and Eosin (H&E) and followed by immunoperoxidase desmin stain. Results: The amount per high power field of the blood and lymphatic vessels below muscularis mucosae layer, 9 (6-12), was significantly higher than that above muscularis mucosae layer, 7 (5-10) (p < 0.05). The cancer high grade (grade 3) in group B had also significantly higher percentage than that in group A, 30.4:5.0 (p < 0.05). Moreover, the recurrent rate (recurrent > 2) in group B had also a significantly higher percentage than that in group A, 21.4:4.0 (p < 0.05). Conclusion: The present study has confirmed previous findings that not all muscularis mucosae layers (about 50%) were found in the biopsy specimens. The findings of superficial urothelial cancer (no invasion to muscularis propria) invading the muscularis mucosae are a warning sign for invasive tumor that needs more aggressive treatment.